Confronting Gender-Based Violence: The State's Accountability In Safeguarding Women And Children's Human Rights - Agustin Widjiastuti; Nafis Dwi Kartiko (PT WIM Solusi Prima, 2023)
This research aims to analyse the conditions and obstacles faced by both groups in the context of human rights violations, as well as provide practical suggestions to improve their protection. The research method used is normative legal methodology, which involves the examination and analysis of legal standards in the literature. A conceptual approach was taken through an exploration of ideologies and teachings that generate legal terminology. Primary and secondary legal materials were collected through inventory, classification, and systematics, with a deduction method for analysis. The results emphasise the need for a comprehensive strategy that considers legal, social, cultural and psychological aspects. The research also suggests the need for cooperation between the government, civil society and relevant institutions to create an environment conducive to the protection of women's and children's rights. The implication of this research is the need for a comprehensive approach in legal policy formulation, which not only focuses on legal aspects but also considers social, cultural, and psychological factors. The research emphasises the importance of increasing public awareness and understanding of human rights, as well as the need to strengthen legal and policy institutions. There is a need to improve the competence of law enforcement and the judiciary, as well as to involve various stakeholders in formulating policies that are more in line with gender issues and the needs of children.